Pharmacological Polarization of Tumor‐Associated Macrophages Toward a CXCL9 Antitumor Phenotype - Noah Enbergs; Elias A. Halabi; Anne‐Gaëlle Goubet; Kelton Schleyer; Ina R. Fredrich; Rainer H. Kohler; Christopher S. Garris; Mikaël J. Pittet; Ralph Weissleder (Advanced Science, 2024)
Abstract Tumor‐associated macrophages (TAM) are a diverse population of myeloid cells that are often abundant and immunosuppressive in human cancers. CXCL9Hi TAM has recently been described to have an antitumor phenotype and is linked to immune checkpoint response. Despite the emerging understanding of the unique antitumor TAM phenotype, there is a lack of TAM‐specific therapeutics to exploit this new biological understanding. Here, the discovery and characterization of multiple small‐molecule enhancers of chemokine ligand 9 (CXCL9) and their targeted delivery in a TAM‐avid systemic nanoformulation is reported. With this strategy, it is efficient encapsulation and release of multiple drug loads that can efficiently induce CXCL9 expression in macrophages, both in vitro and in vivo in a mouse tumor model. These observations provide a window into the molecular features that define TAM‐specific states, an insight a novel therapeutic anticancer approach is used to discover.